Social Services Planning in Rural Areas: A Theoretical Review - Djarot S. Widyatmoko (Universitas Muhammadiyah Surakarta, 1991)
Nowadays, the comprehensive and integrated rural development concept has been considered as the right approach in order to combat the root of rural poverty. By its main concern on area planning, i. e. the availability of planning apparatus at local (regional) level, comprehensive local (rural) resource analysis, and multi-disciplinary approach, it is expected that the weakneses of centralized planning which, among others, concentrates on economic growth can be reduced or even eliminated. This paper tries to explain the place of social service planning in the rural development concept above. The approach used is by discussing the place of service planning in the national development policies; collective decision making system, especially related to planning procedure and process; and social service problems in rural areas.